VAPOR-LIQUID EQUILIBRIUM (VLE) WATER-ETHANOL FROM BULRUSH FERMENTANTION - Sari, Ni Ketut (Jurnal Teknik Kimia, 2010)
Liquid-vapor equilibrium date need in separation process for example distillation, extraction,absorbsi processes, binary system or multi component system. Be inside Liquid-vapor equilibriumdate can be used for strenght what is mixture faundation azeotropic or zeotropic mixture. For canbe Liquid-vapor equilibrium date ethanol-water, generaly used raw material wich pro analitic (pro analitic ethanol), In research will example for used raw material wich technical that isbulrush fermentation yield wich already distillation (technical ethanol). This research can beliquid-vapor equilibrium date binary system ethanol-water, verification of eksperiment yield withliterature date, and can be temperature date in distilate and in bottom binary system ethanolwater.Research used device of Still Othmer Glass, raw material ethanol wish used that istechnical and pro analitic with variable of ethanol feed composition that is 0 ; 0.2 ; 0.4 ;0.6 ;0.8 ;1(mol fraction) and constant pressure 300 bar. Ethanol yield wich used analysis usedspectrofotometer pharo 100. From yild research wich used, than liquid-vapor equilibrium datebinary system ethanol-water direction azeotropic point at ethanol composition 0.98 mol fraction,and date wish used can be used in calculation at distilation, extraction, absorbsi processes.Keywords : Azeotropes, fermentation, bulrush, binary system.